Pengaruh Operasi Pasar Perum BULOG terhadap Stabilitas Harga Beras di Provinsi Bali - PUSPAKA, MADE MANIKA; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p25, 2022)
The Effect of Perum BULOG’s Market Operation towards Rice Price Stability in the Province of Bali Rice as a strategic food commodity has an important role in improving food security and stabilizing the economic, social, and political aspects of the Bali Province people. The stability of rice price is one of the problems considered and finds a way out by the government. To stabilize the rice price, the Government through The Division of Regional Logistics Agency of Bali (BULOG Divre Bali) conducted Rice Market Operations. The purpose of this study was to perceive, (1) the condition of retail price stability of medium quality rice and (2) the effect of BULOG’s Rice Market Operation in 2015-2017. The method of data collection in this study used the study literature, interview, and documentation. The data analysis method used coefficient of variation and descriptive analysis. The results showed that in 2015-2017 the price stability of medium rice in The Province of Bali was quite stable. BULOG’s Rice Market Operations had effect on stabilizing the rice price at the consumer level in Province of Bali. In order to increase the effectiveness of the Rice Market Operations activities in stabilizing the rice price in Bali Province, BULOG needs to be more selective in choosing the location of Rice Market Operations and there needs to be good coordination between the government and BULOG so the Rice Market Operation activities is effective in stabilizing rice prices in The Province of Bali.